In silico Study of the Antidiabetic Potential of Alkaloid Compounds from the Roots of Acalypha indica: Molecular Docking and ADMET Prediction - Ahmad Chandra Lakasan; Suleman Duengo; Arviani; Wenny JA Musa; Anderson Arnold Aloanis; Deasy Natalia Botutihe (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Oral Type 2 Diabetes Mellitus (T2DM) therapy gastrointestinal side effects encouraged bioactive alternative exploration via Acalypha indica root alkaloids. This study aimed to evaluate Acalypha indica root alkaloids detected by LC-HRMS against α-glucosidase using molecular docking and ADMET evaluation. Ligand structures were optimized via ChemDraw 3D while 2QMJ receptor preparation was conducted using Discovery Studio Client and AutoDock Tools. Parameters were validated through redocking with RMSD <2 Å. Molecular docking was performed using AutoDock Vina with interaction visualization via Discovery Studio Visualizer and PyMOL while pharmacokinetic profiles were predicted using ADMETlab. Results identify compound (1) as the most potent inhibitor with ΔG -9.47 kcal/mol surpassing acarbose stability. Visualizations confirm hydrophobic interaction strengthening at key catalytic residues Asp443 and Asp542 indicating a competitive inhibition mechanism. Compound (1) selection as the primary candidate is based on high affinity and genotoxic safety due to mutagenicity absence in AMES parameters. Compound (1) ADMET characteristics show low intestinal permeability advantageous for local action in the intestinal lumen similar to acarbose. This study recommends compound (1) as a potential antidiabetic candidate for further testing although structural optimization is required to mitigate organ toxicity risks at advanced clinical stages.